2016
DOI: 10.1111/avj.12468
|View full text |Cite
|
Sign up to set email alerts
|

NT‐proBNPand cardiac troponin I concentrations in dogs with tick paralysis caused byIxodes holocyclus

Abstract: This study did not detect significant cardiac involvement in dogs with tick paralysis induced by I. holocyclus. Evidence for reduced preload in dogs with tick paralysis was provided by lower NT-proBNP concentrations compared with control dogs. Severe hypoxaemia may not be a significant component of the clinical picture in many of the dogs presenting with tick paralysis. Dogs with severe hypoxaemia may have loss of cardiomyocyte integrity, reflected by elevated cTnI concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Echocardiography is currently the preferred method to assess structural and functional cardiac disease, 42 and the present study suggests that cardiac function may play a role in the development of cachexia in debilitated green sea turtles. To more clearly understand the link between cachexia and cardiac function in green sea turtles, the use of specialised biomarkers to assess myocyte damage and preload 43 in affected animals would be of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Echocardiography is currently the preferred method to assess structural and functional cardiac disease, 42 and the present study suggests that cardiac function may play a role in the development of cachexia in debilitated green sea turtles. To more clearly understand the link between cachexia and cardiac function in green sea turtles, the use of specialised biomarkers to assess myocyte damage and preload 43 in affected animals would be of interest.…”
Section: Discussionmentioning
confidence: 99%
“…A study of 46 dogs with TP demonstrated low protein pulmonary oedema due to reversible diastolic dysfunction causing left-sided congestive heart failure ( 16 ). However, a subsequent study of 80 dogs with TP and 31 healthy control dogs failed to show an increase in the biomarker cardiac troponin I, suggesting an absence of myocardiocyte injury in animals affected with the disease ( 103 ).…”
Section: Management Of the Ventilated Patientmentioning
confidence: 99%
“…Most importantly, it is necessary to delay degradation (like hemolysis, for instance) during collection procedures and transportation to a laboratory. Furthermore, samples have to be centrifuged and kept under refrigeration immediately after collection [ 5 , 9 , 31 , 34 - 37 ]. Sample storage methods also greatly influence the values of NT-proBNP in serum.…”
Section: Laboratory Evaluationmentioning
confidence: 99%